A study of 113 cases of genital ulcerative disease and urethral discharge syndrome with validation of syndromic management of sexually transmitted diseases - Bhavsar, Chintan (Medknow Publications & Media Pvt Ltd, 2014)
AIMS: To validate syndromic management of cases having genital ulcerative disease (GUD) and urethral discharge syndrome (UDS). MATERIALS AND METHODS: A study of 113 cases of GUD and UDS was carried out in the Department of Skin and VD from March 2011 to August 2012. All cases having history and clinical evidence suggestive of GUD and UDS were included in the study. RESULTS: According to syndromic diagnosis, GUD herpetic syndrome was the most common 71 (62.27%), followed by GUD non-herpetic syndrome 25 (21.89%) and UDS 17 (14.91%). Out of 71 cases clinically diagnosed as GUD herpetic, 16 (22.53%) were validated by immunoglobulin M (IgM) anti herpes simplex virus-2 (HSV) serology, 14 (19.71%) by Tzanck smear and 3 (4.22%) by both. 24 (33.80%) were Reactive plasma Reagin (RPR)(<1:8) reactive and trepenomma palidum haem-agglutination positive. Out of total 25 clinically diagnosed GUD non herpetic cases, 22 (88%) were validated by laboratory tests Out of 17 cases of UDS, 15 (88%) were validated by smear. CONCLUSION: Sensitivity and specificity of clinically diagnosed syndrome is not so high particularly for GUD herpetic syndrome Continuous monitoring of diagnostic component of syndromic approach is key to success of STD control program.